Business Model Canvas (BMC) Analysis of Rumah Pangan PNM at PNM Purwokerto Branch - Rohmat Agus Pranoto; Acong Dewantoro Marsono (Sean Institute, 2026)
Community-based food security initiatives require sustainable and inclusive business models to ensure long-term impact and social empowerment. Rumah Pangan PNM Purwokerto Branch was established as a social enterprise program aimed at strengthening local food resilience while empowering women through community participation. This study aims to analyze the existing business model of Rumah Pangan PNM using the Business Model Canvas (BMC) framework and to formulate strategic development directions to enhance its sustainability and social impact. This research employs a qualitative descriptive approach within an interpretive paradigm. Data were collected through in-depth interviews, focus group discussions, observations, and document analysis involving program managers, institutional partners, and community members, and were analyzed using thematic and BMC-based analytical techniques. The results indicate that the existing model has implemented all nine BMC elements in an interconnected manner, with strong value propositions rooted in community empowerment, institutional collaboration, and the provision of nutritious local food. However, the model remains highly dependent on a limited number of institutional offtakers, lacks product diversification, and has restricted market reach. This study proposes a development framework emphasizing customer segment expansion, value-added product innovation, digital-based distribution channels, partnership strengthening, and resource optimization. These findings demonstrate that BMC can effectively support the transformation of community-based food initiatives into more adaptive and sustainable social enterprises, contributing to both economic viability and social empowerment.